Predictors for survival of patients with squamous cell carcinoma of unknown primary in the head and neck region - Wagner, Steffen; Langer, Christine; Wuerdemann, Nora; Reiser, Susanne; Abing, Helen; Pons-Kühnemann, Jörn; Prigge, Elena-Sophie; Knebel Doeberitz, Magnus von; Gattenlöhner, Stefan; Waterboer, Tim; Schroeder, Lea; Arens, Christoph; et al. (Cancers, 2023)
Background: Human papillomavirus (HPV) status is the most important predictor of survival in oropharyngeal squamous cell carcinoma (OPSCC). In patients with cervical lymph node metastases of squamous cell carcinoma of unknown origin (CUPHNSCC), much less is known. Methods: We assessed a consecutive cohort of CUPHNSCC diagnosed from 2000-2018 for HPV DNA, mRNA, p16INK4a (p16) expression, and risk factors to identify prognostic classification markers. Results: In 32/103 (31%) CUPHNSCC, p16 was overexpressed, and high-risk HPV DNA was detected in 18/32 (56.3%). This was mostly consistent with mRNA detection. In recursive partitioning analysis, CUPHNSCC patients were classified into three risk groups according to performance status (ECOG) and p16. Principal component analysis suggests a negative correlation of p16, HPV DNA, and gender in relation to ECOG, as well as a correlation between N stage, extranodal extension, and tobacco/alcohol consumption. Conclusions: Despite obvious differences, CUPHNSCC shares similarities in risk profile with OPSCC. However, the detection of p16 alone appears to be more suitable for the classification of CUPHNSCC than for OPSCC and, in combination with ECOG, allows stratification into three risk groups. In the future, additional factors besides p16 and ECOG may become important in larger studies or cases with special risk profiles.
Gesehen am 01.08.2023